Introduction to thematic section_From the Victorian Era to the American Experiment: Mythic Foundational Narratives in Video Games - Teresa Pereira (VIA PANORAMICA: Revista de Estudos Anglo-Americanos / A Journal of Anglo-American Studies, 2025)
Introduction to thematic section From the Victorian Era to the American Experiment: Mythic Foundational Narratives in Video Games